9(3x+12)=10(2x+15)

Simple and best practice solution for 9(3x+12)=10(2x+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3x+12)=10(2x+15) equation:


Simplifying
9(3x + 12) = 10(2x + 15)

Reorder the terms:
9(12 + 3x) = 10(2x + 15)
(12 * 9 + 3x * 9) = 10(2x + 15)
(108 + 27x) = 10(2x + 15)

Reorder the terms:
108 + 27x = 10(15 + 2x)
108 + 27x = (15 * 10 + 2x * 10)
108 + 27x = (150 + 20x)

Solving
108 + 27x = 150 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
108 + 27x + -20x = 150 + 20x + -20x

Combine like terms: 27x + -20x = 7x
108 + 7x = 150 + 20x + -20x

Combine like terms: 20x + -20x = 0
108 + 7x = 150 + 0
108 + 7x = 150

Add '-108' to each side of the equation.
108 + -108 + 7x = 150 + -108

Combine like terms: 108 + -108 = 0
0 + 7x = 150 + -108
7x = 150 + -108

Combine like terms: 150 + -108 = 42
7x = 42

Divide each side by '7'.
x = 6

Simplifying
x = 6

See similar equations:

| (3x-4)-(5x-3)= | | 20x+6x-2= | | r-7.9=7.5 | | 3+x=22-2 | | 6x-2=20x | | P+7=35 | | x-(-12)=17 | | 3x^3-x^2+21x-7=0 | | -9r+6t-s-5r+s+4t-t+2s-r= | | 3x^2+x-57=3 | | fx=10x^3 | | 2x+y=-d | | 6x-2+20x= | | 3x-23=4x-2 | | -3(-x+5)+7(-x)+5(-5x-2)+25= | | 5y+4=8y-1 | | 8w-12w=32 | | N-3=3n+5 | | X=6x^2-42x-180 | | 2x-4y=3y+10x | | 7+3x-12=3x-5 | | 4x-5+3x+20= | | X+6=2+5x | | 52*1.20= | | 1=0.4x-0.7x-20 | | 5*1.20= | | -7(-x+5)+8(-x)+3(-5x-3)+44= | | x-(x*.25)=18.75 | | -5-2n=11 | | 3x^3-2x-6=0 | | y+7x=49 | | 70=180 |

Equations solver categories